Contribuições de Dom Luciano José Cabral Duarte ao ensino superior sergipano (1950 1968) - Lima, Fernanda Maria Vieira de Andrade (2009)
This study aims to analyze the contributions of Dom Luciano José Cabral Duarte to the higher education in Sergipe, more specifically, his work in the Faculdade Católica de Filosofia de Sergipe FAFI and in the Universidade Federal de Sergipe, having been chosen the years between 1950 and 1968 for the research, once it is understood that, during this period, both institutions were created and also for the fact that the work of that priest, in the educational field, was more remarkable. Aiming to contribute to the construction of the history of higher education in Sergipe, we believe that the period of time chosen to the investigation in this work is short; however, the reasons found for the choice were attributed from the effects idealized for this research. This investigation is based on the presuppositions from the History of Education and the Cultural History and uses biographical sources, bibliographical. iconographical, interviews, conferences, electronic articles, documents from public and private archives, correspondences, information, newspaper and magazines to deepen the knowledge of the object of analysis, idealizing an analysis that may contribute to the future studies on the History of Education, more specifically, to the higher education in Sergipe, viewing the actions of a representative from the Catholic Church of this state.